2017
DOI: 10.4049/jimmunol.1601672
|View full text |Cite
|
Sign up to set email alerts
|

Raf Kinase Inhibitor Protein Preferentially Promotes TLR3-Triggered Signaling and Inflammation

Abstract: Raf kinase inhibitor protein (RKIP) protects against host immunological responses in nematodes and Whether RKIP functions in innate immune responses in mammals remains unknown. In this article, we report that RKIP preferentially regulates the TLR3-mediated immune response in macrophages. RKIP deficiency or silencing significantly decreases polyinosinic:polycytidylic acid [Poly(I:C)]-induced IFN-β, IL-6, and TNF-α production without affecting the counterpart induced by LPS or CpG. Compared with their wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…TLR3 is a unique member of the TLR family that is located in endosomal compartments or on the cell surface [ 27 ]. TLR3 usually recognizes pathogen-derived nucleic acids and recruits an adaptor protein to induce interferon-ß release [ 17 , 28 ]. Recently, several studies investigated the essential roles of TLR3 activation in the amplification of inflammatory responses and cytokine release in response to HMGB1 [ 17 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…TLR3 is a unique member of the TLR family that is located in endosomal compartments or on the cell surface [ 27 ]. TLR3 usually recognizes pathogen-derived nucleic acids and recruits an adaptor protein to induce interferon-ß release [ 17 , 28 ]. Recently, several studies investigated the essential roles of TLR3 activation in the amplification of inflammatory responses and cytokine release in response to HMGB1 [ 17 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…RKIP is well established as an inhibitory molecule in oncological processes (14). We recently demonstrated that RKIP is involved in colitis and antiviral innate immune responses, indicating that RKIP functions as an important mediator in immune response (15)(16)(17). Here, we found that RKIP deficiency in mast cells does not affect the development of mast cells or the expression of surface markers, including FceRI and c-Kit, but significantly inhibits the IgE−FceRI-mediated early-phase mediators, including histamine and β-hexosaminidase, and late-phase mediators, such as type 2 cytokines, proinflammatory cytokines, and other related chemokines (CCL1, CCL2).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our findings not only suggest that RKIP plays an important role in controlling mast cell-mediated allergic responses but also provide insight into therapeutic targets for mast cell-related allergic diseases. (17). Therefore, RKIP functions as a physiological and pathological regulator more than as a tumor suppressor.…”
Section: Significancementioning
confidence: 99%
“…In addition, RKIP-deficient mice produced fewer pro-inflammatory cytokines and type I interferons and were more resistant to Poly(I:C)-induced death. It was further demonstrated that Poly(I:C) treatment induces RKIP phosphorylation at S109, being this action required for RKIP to promote TLR3-mediated signalling and inflammation [62].…”
Section: Rkip and Inflammationmentioning
confidence: 98%